Evaluation of the structural reliability of a grandstand subjected to anthropic loads (2016)
(Eng) The presence of crowds in soccer stadia produce dynamic loads which can in turn induce changes to the dynamic properties of the structural system and cause vibrations that exceed admissible comfort levels. The South Grandstand of the Pascual Guerrero Olympic Stadium in Cali, Colombia, has been the traditional stand for the rowdiest groups of fans during the soccer season, making it ideal for studies on human-structure interaction and structural reliability. This paper describes the analysis of the structural reliability of the grandstand using serviceability limit states recommended in international standards,. The methodology included the characterization of the dynamic response of the structure during several soccer matches, the formulation of the load functions for people jumping, simulations of the location of spectators in the stand using fuzzy logic and the incorporation of this information in a finite element model that was updated with experimental results. Structural reliability indexes were obtained for the response of the grandstand to anthropic loads.